Supported to perform: sports bras and breast volume do not impair cycling performance in females - Illidi, Camilla R.; Jensen, Dennis (Frontiers in Sports and Active Living, 2024)
Introduction: Despite the importance of sports bras for women’s comfort during exercise in people with breasts, concerns persist regarding their potential effects on athletic performance. Discrepancies in previous studies necessitate a closer examination of the interaction between sports bras, breast volume, exertional symptoms, and exercise performance. Methods: Twenty-three recreationally-active, normal bodyweight females completed three 10-km time-trials on a cycle ergometer on three separate occasions in a randomized order, while wearing a professionally fitted high-support sports bra, a professionally fitted low-support sports bralette, or a personal, self-selected sports bra. Performance was quantified as the time to complete the 10-km distance. Cardiorespiratory and symptom responses were measured throughout. Results: Participants were grouped by their estimated breast volumes (small: mean ± SD 284 ± 38 mL, median bra size: 32C; large: 560 ± 97 mL, 34DD; p = 0.002, g = 3.84). The average time-trial duration was 23.1 ± 3.1 min and comparable across breast volume groups and sports bra conditions (between-group: p = 0.794, ηp2<0.01; between-bras: p = 0.273, ηp2<0.01). Notably, larger-breasted participants experienced stronger symptoms of chest tightness (p = 0.042, ηp2 = 0.18), which were associated with their ratings of perceived exertion and breathlessness (intensity and unpleasantness). Irrespective of breast volume, the high-support sports bra also evoked stronger symptoms of chest tightness (p = 0.039, ηp2 = 0.15). Discussion: Stronger symptoms of chest tightness associated with larger breast volumes or high-support sports bras do not impede performance during self-paced non-weight-bearing exercise in recreationally-active females.